EXPERIMENTAL RESEARCH OF THE INFLUENCE OF VARIOUS TYPES OF SOLAR COLLECTORS FOR PERFORMANCE SOLAR DESALINATION PLANT - Rakhmatulin I.R. (Problems of the Regional Energetics, 2014)
The article discusses the possibility of using renewable energy for water purification. Results of analysis of a preferred energy source for a water purification using installed in places where fresh water shortages and a lack of electrical energy. The possibility of desalination of salt water using solar energy for regions with temperate climate. Presented desalination plant working on energy vacuum solar collectors, principles of action developed by the desalination plant. The experimental results of a constructed distiller when working with vacuum glass tubes and vacuum tubes with copper core inside. Conclusions about the possibility of using solar collectors for water desalination, are tips and tricks to improve the performance of solar desalination plant.